Incidence and spread of insects from bucket elevator leg boots - Tilley, Dennis Ray (Kansas State University, 2013)
In commercial grain elevators and feed mills, the boot and pit areas contribute to commingling of insects with grain that moves through the elevator leg. A pilot-scale bucket elevator leg with a modified removable boot, or slip-boot, was used to measure the magnitude of commingling as a function of stored-product insect density and boot holding time in tests with wheat and corn. Pilot-scale tests showed that clean grain transferred over infested boots was infested with about 1 insect/kg when transferred immediately after the boot was infested; this increased to 2 insects/kg after incubating the boot for 8 wk. Larger numbers of kernels with internal infestations were picked up by clean grain during transfer compared with externally infesting insects, because the mobility of the latter enabled them to move away from buckets during transfer. Monthly surveys over two years at elevators and feed mills revealed several stored-product insects in grain residues from the boot and pit areas and bulk load-out samples. Insect densities in the boot and pit areas were impacted by seasonal temperatures and facility sanitation practices. Recommended sanitation guidelines for the boot and pit areas include: (1) boot residual grain clean-out every 30 d, (2) removal of grain spillage and floor sweepings from the pit area, and (3) proper disposal of boot and pit residual grain. Facilities following these sanitation guidelines could avoid costly grain discounts, increase income of the business operation and minimize or prevent cross contamination of clean grain by infested grain in the boot and pit areas.
Keywords: Bucket elevators; Stored-grain insects; Sanitation; Agriculture, General (0473)